PENGARUH PENAMBAHAN BOKHASI KUBIS (Brassica oleracea var. capitata) TERHADAP PERTUMBUHAN BAWANG PUTIH (Allium sativum L) PADA TANAH PODZOLIK MERAH KUNING - Frona, Wike Samira; Zein, Anizam; Vauzia, Vauzia (IAIN Batusangkar, 2016)
Garlic (Allium sativum. L) constitute one of plant which requisition high it at marketing because has a lot of benefit as condiment of cookery, as salving as and effects anti microbe. For meeting that marketing requisition needs improved its production. One of problem in garlic instilling is media plant out that has to increase low fecundity as soiled as podzolik tingles to yellow (PMK). Therefor needs effort for added organic fertiliser, one of that potentially is cabbage waste (Brassicaoleracea var. capitata) one that made by bokhasi with EM4'S application (Effective Microorganisms 4). Base that thing was done research about bokhasi's increase influence cabbage (Brassicaoleraceavar. capitata) to garlic growth (Allium sativum. L) on podzolik's earth tingles to yellow. Research is done on January until May 2015, at Bagiriak's Stone, Elongated allergy and Botanical Physiology Laboratory, FMIPA UNP. This experiment research utilize random design furnished with 5 conducts and 4 dry runs. Conduct that is given is distinctive dosed bokhasi's manure cabbage which is conduct A = 0 g / polibagbokhasi cabbages, conduct b = 250 g / polibag, conduct c = 500 g / polibag, conduct d. = 750 g / polibag, and conduct e = 1000 g / polibag. Observed parameter is tall plant, total helai leaf, total fang / corm, wet weight, dry weight, total root and pH is earth. dianalisis's data by use of ANOVA and lanjut DNMRT's quiz on level 5%. Result observationaling to point out that bokhasi's application cabbage significanting to high, total helai leaf, total fang / corm, wet weight, dry weight, and plant root amount garlic and not give reality influence on pH earth.Key words: bokhasi, cabbage, garlic, podzolik's earth tingles to yellow